2023
DOI: 10.3390/pharmaceutics15010264
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and In Vitro Evaluation of Mucoadhesive Sustained Release Gels of Phytoestrogen Diarylheptanoids from Curcuma comosa for Vaginal Delivery

Abstract: Diarylheptanoids (DAs) characterized by a 1,7-diphenylheptane structural skeleton are considered a novel class of phytoestrogens. The DAs available in Curcuma comosa Roxb. (C. comosa) extract demonstrated significant estrogenic activities both in vitro and in vivo. This study aimed to develop and comprehensively evaluate a mucoadhesive vaginal gel for the sustained release of DAs. Different mucoadhesive polymers as gelling agents were investigated. C. comosa ethanolic crude extract was used as a source of DAs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…In a study, it was shown that viscosity, hardness, and adhesiveness increased with the increase in polymer concentration of the gels prepared with chitosan (0.5-1%) [48]. In another study using polycarbophil or HPMC, they showed that the hardness and compression of vaginal mucoadhesive gel formulations increased as their viscosities increased [49]. The findings obtained are compatible with the literature.…”
Section: Mechanical Propertiessupporting
confidence: 84%
“…In a study, it was shown that viscosity, hardness, and adhesiveness increased with the increase in polymer concentration of the gels prepared with chitosan (0.5-1%) [48]. In another study using polycarbophil or HPMC, they showed that the hardness and compression of vaginal mucoadhesive gel formulations increased as their viscosities increased [49]. The findings obtained are compatible with the literature.…”
Section: Mechanical Propertiessupporting
confidence: 84%